Incidencia de la forma de arcos dentarios en los estudiantes de la Carrera de Odontología de la Universidad Nacional de Chimborazo - Guevara Rodríguez, Lizeth Carolina (2017)
The purpose of this paper is to determine the incidence of the shape of dental arches of the oral cavity. The research was conducted in 60 male and female who study in the School of Dentistry of the National University of Chimborazo, for which it was made the dental-medical history and the clinic file, the beginning of the research was carried out with the taking of impressions of alginate of the maxilla upper jaw and the mandible lower jaw, subsequently the castings were made in extra hard plaster of Paris, and in this way to determine the type of dental arcade according to the determined table given by Chuck, in whom a sheet of acetate with predetermined shapes was made to verify the exact shape of the arcades of each patient, it is expected to find a greater incidence in the square shape of the dental arches. The results showed that there is a greater predominance of the quadrilateral form with a percentage of 48.30 followed by the ovoid form with 38.30% and the narrow with 13.30% in the maxilla, while in the mandible presented a percentage of 36.70 in the form Narrow, followed by the ovoid shape with a percentage of 35 and finally the square shape with a percentage of 28.30. %. And in general without taking into account gender studied predominance square shape with a 38% followed by ovoid shape with a 37%. We consider that these results are due to the population that was studied.